THE AUTOBIOGRAPHICAL FOUNDATION OF VASYL KARHUT'S FINE PROSE - Vasylchuk, Mykola (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
The article examines the features of the artistic prose of the Ukrainian writer, phytotherapist, personal physician of Metropolitan Andrey Sheptytskyi, political prisoner Vasyl Karhut (1905–1980). The stories "Flame Whirlwind" and "Winged Land" are analyzed, which reflect the complex and ambiguous period of Ukrainian history of the late 1930s - mid-1940s. It is traced how the writer transforms living material of modern times into artistic texts. It is noted that the writer becomes a passionate exposer of the essence of anti-human political regimes.At the same time, both stories are a requiem for those who preserved their national and human essence in the conditions of that time. It is shown that these works are both artistic texts and documents in which the author recorded the thoughts and feelings of his contemporaries.